The melanocortin receptors and their accessory proteins - Ramachandrappa, Shwetha (Frontiers Media S.A., 2013)
The five melanocortin receptors (MCRs) named MC1R–MC5R have diverse physiological roles encompassing pigmentation, steroidogenesis, energy homeostasis and feeding behavior as well as exocrine function. Since their identification almost 20 years ago much has been learnt about these receptors. As well as interacting with their endogenous ligands the melanocortin peptides, there is now a growing list of important peptides that can modulate the way these receptors signal, acting as agonists, antagonists, and inverse agonists. The discovery of melanocortin 2 receptor accessory proteins as a novel accessory factor to the MCRs provides further insight into the regulation of these important G protein-coupled receptor.